Incarcerated Mothers: Trauma and Attachment Issues. (2nd January 2017) - Harris, Marian S.
ABSTRACT: Although men comprise the largest portion of the prison population in the United States, the number of women in prison has increased more than 800% during the past three decades. More than 60% of these women are mothers of children under 18 years of age. There continues to be a gap in our knowledge base regarding mothers who are incarcerated. In this study, unresolved issues of trauma and attachment are explored for 28 incarcerated mothers involved with the child welfare system. Data were collected using the Trauma Attachment and Belief Scale (TABS) and the Adult Attachment Interview (AAI). Findings from the TABS revealed scores of average and high average in beliefs related to five need areas that are sensitive to the effects of traumatic experiences, namely self-safety, self-trust, self-esteem, self-intimacy, and self-control. Most participants were classified as disorganized/disoriented based on their narrative responses to questions from the AAI protocol. Implications for the results are discussed.